Negative reinforcement smoking outcome expectancies are associated with affective response to acute nicotine administration and abstinence - Robinson, Jason D. (2011)
BACKGROUND: Negative affect is an important predictor of smoking behavior, and many smokers believe that smoking reduces negative affect. However, it is unclear whether such beliefs, known as negative reinforcement smoking outcome expectancies (NRSOE), are associated with changes in negative affect in response to nicotine deprivation and administration. METHODS: Smokers (N = 114) participated in 4 sessions that balanced overnight smoking deprivation (12-hr deprived vs. ad lib) and nasal spray administration (nicotine vs. placebo). Corrugator supercilii (COR) EMG, skin conductance (SCR), and in-session ratings were collected while the participants viewed affective, cigarette-related, and neutral slides. Retrospective questionnaire data were collected prior to slide viewing. NRSOE were determined using the Smoking Consequences Questionnaire-Adult Nicotine Affect Reduction scale (SCQ-NAR). RESULTS: High scores on the SCQ-NAR were associated with smaller COR EMG to unpleasant slides following nicotine nasal spray administration compared to placebo spray, regardless of overnight deprivation. Smokers who had high scores on the SCQ-NAR had smaller SCR, following nicotine nasal spray administration compared to placebo spray, but only after overnight deprivation. The in-session ratings and retrospective questionnaire measures indicated that smokers who had high scores on the SCQ-NAR experienced greater negative affect and craving, and less positive affect, than smokers with low scores on the SCQ-NAR, regardless of nicotine exposure. CONCLUSIONS: Our questionnaire results suggest that while smokers who have high NRSOE self-report greater overall levels of negative affect and craving, while the psychophysiological data suggest that such smokers may experience negative affect reduction when blindly administered a dose of nicotine.